Mathematical model and method of complex organizational diagnostic - Mikhnenko, Pavel Aleksandrovich (Serbian Journal of Management, 2020)
The paper is devoted to the complex diagnostic of structural and cultural properties of organizations. The study reveals the new diagnostic tool – the conjunctive matrix of the coordination-cultural profile of the organization. The concept of coordination mechanisms by Mintzberg was used for diagnostics of structural-managerial characteristics of organizations. To describe the organizational culture was used the model by Cameron and Quinn (“The Competing Values Framework”). For evaluation of explicitness of the coordination profile and the profile of organizational culture were used the coefficients of homogeneity. Depending on the ratio between the coefficients of homogeneity of the coordination profile and the cultural profile were substantiated four basic types of coordination-cultural profile: “Accurate Tuning”, “Coordination Groundwork”, “Culture Groundwork” and “Searching for a Basis”. The study of twenty-two companies reveals that coordination-cultural profile “Accurate Tuning” provides the maximum economic efficiently of organizations.
Keywords: organizational diagnostic; coordination mechanisms; organizational culture; coordination-cultural profile; conjunctional matrix